Կարմիր գունանվան դերը հայ և ճապոնական լեզվամշակոիյթներում - Բաբայան, Տաթև (Քոփի Փրինթ)
Language is closely related to the culture, worldview and identity of any nation. Being an important element of the culture of many nations, the red color has found its unique role in the languaculture of nations as well. Armenian and Japanese are no exceptions. The “red” color name has many metaphorical meanings in the mentioned languages. Among the most used ones in Armenian are: happiness, marriage, festive mood, blood, pain, etc. In Japanese: purity, luck, beautiful, marriage, obvious, deficit, etc. Although Armenian and Japanese belong to different language families and have different syntax, some phrases involving the "red" color name, have similar metaphorical meaning or phrase structure.
Keywords: Գունագիտություն; Մշակույթ